Knowledge and attitude study among the nursing staff working in a tertiary care hospital in Southern India - B., Pavithra M.; Shamanewadi, Amrita N.; Madhukumar, Suwarna (International Journal Of Community Medicine And Public Health, 2019)
Background: Hand hygiene is recognised as one of the leading measure to prevent cross transmission of micro-organisms. Inadequate hand hygiene practices are common cause of nosocomial infections. Nurses are considered as the “nucleus of health care system” Because of the time they spend with patients than any other health care workers. Hence their compliance with hand washing guidelines seems to be more vital in preventing the disease transmission among patients. Methods: Despite the simplicity of the procedure, compliance with hand hygiene among health care providers in particular nurses is as low as 40%. This study aims at assessing knowledge, attitude and practice of hand hygiene of the nursing staff working in a tertiary care hospital. Results: Among the 140 study participants 74% were female nurses. Majority of the study participants (78%) had average knowledge of hand hygiene in the pre-test session The health education and training session on correct hand hygiene methods significantly(p<0.001) improved the knowledge and attitude of the nursing staff, during the post-test session 87% of the nurses had good knowledge and 100% had positive attitude. Conclusions: Our study shows the importance of improving the current training programmes targeting the hand hygiene practices among nursing staff. Hand hygiene training sessions need to be conducted more frequently with continuous monitoring and performance feedback to encourage them and their fellow nurses to follow correct hand hygiene practices.